2005
DOI: 10.3748/wjg.v11.i17.2653
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of apoptosis related gene Fas ligand in human hepatocellular carcinoma cells and its significance in apoptosis

Abstract: Fas ligand is an apoptotic pathway of HCC cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…FasL is a key protein that triggers the extrinsic apoptosis pathway, and its expression is regulated by many transcriptional factors such as Jun, NF‐κB, NFAT, EGR‐3, and SP1 in human tumors . Previous studies demonstrated that transfection of FasL into HepG2 cells induces apoptosis . The extrinsic and intrinsic apoptotic pathways are mediated by different caspases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FasL is a key protein that triggers the extrinsic apoptosis pathway, and its expression is regulated by many transcriptional factors such as Jun, NF‐κB, NFAT, EGR‐3, and SP1 in human tumors . Previous studies demonstrated that transfection of FasL into HepG2 cells induces apoptosis . The extrinsic and intrinsic apoptotic pathways are mediated by different caspases.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47][48] Previous studies demonstrated that transfection of FasL into HepG2 cells induces apoptosis. 49 The extrinsic and intrinsic apoptotic pathways are mediated by different caspases. Caspase 8 is the initiator in the extrinsic apoptotic pathway, while caspase 9 is the initiator in the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, FasL, an important trigger for Fasinduced cell death, is commonly seen elevated in liver tissue and serum in both patients with cirrhosis and HCC. However, higher levels of FasL were seen in patients with cirrhosis alone compared to those with HCC, and more abundant in peritumor tissue compared to tumor tissue within the diseased liver [114,116,117]. Other cytokines and chemokines which may play important roles in the progression phase of HCC, however, may be only minimally expressed or not present at all during the initial stages of the disease.…”
Section: Non-cellular Factors In the Hbv-associated Hcc Microenvironmentmentioning
confidence: 99%
“…Additionally, Pinti et al , reported an increase in the production of Fas with age [67], while the production of sFasL is consistently reduced [67] and suggested a dissociation between the levels of sFas and sFasL. Further longitudinal studies are warranted in HBV-and HBV/HIV- infected patients to better understand the role sFas and sFasL are playing in HBV-mediated liver disease and whether there is any prognostic value in monitoring sFas and sFasL levels [46, 62, 68].…”
Section: Discussionmentioning
confidence: 99%